The Saturation Dilemma Reconsidered: Role, Challenges and Controversies for Qualitative Research in the Digital Era - Favourate Y. Mpofu (International Journal of Qualitative Methods)
Saturation is a pivotal concept in qualitative research, playing a fundamental role in enhancing the completeness and robustness of qualitative findings. However, the digital era has presented new challenges and heightened the already existing “saturation controversy” in qualitative research. The plethora of digital data sources, the transformation of data collection methods and the increase in the volume of data in this time of “big data” raises questions about the relevance and applicability of the conventional approaches of assessing saturation. This paper discusses the dynamic landscape of qualitative research, digital transformation of qualitative research and implications for the concept of saturation. Additionally, the emerging challenges encountered by qualitative researchers in determining saturation in the digital age due to high volume of data and unstructured datasets are explored as well as the debates surrounding the continued applicability and relevance of the saturation methodological principle. Furthermore, emerging frameworks and strategies for the conceptualisation of saturation in the digital context are discussed, highlighting the possible incorporation of data visualisation and computational techniques to support judgments about saturation. While ethical considerations and issues of ensuring credibility and trustworthiness have always been critical matters in qualitative research, approaches to ensuring good data governance, data privacy, transparency, and data authenticity in the face of saturation in the digital era are imperative. Lastly, the paper examines the wider implications of these developments, the dynamic role of saturation in qualitative research methodologies as well as the opportunities for methodological advancements and interdisciplinary collaboration. The paper is expected to contribute to a comprehensive analysis of the saturation controversy in the digital era, provide guidance on how the challenges, complexities and controversies concerning this critical methodological principle can be addressed and to theoretically contribute to ongoing debate on the transformation of qualitative research practices in the evolving digital landscape.